Zoning and opportunity Spectrum Planning in a Discontinuous Environment : Planning for Tourism and Outdoor Recreation in the Luleå Archipelago, Sweden - Ankre, Rosemarie; Emmelin, Lars (Institutionen för samhällsvetenskap, 2006)
Zoning is generally used as a planning instrument to handle land use conflicts. In recreation planning in Sweden, zoning systems such as the recreation opportunity spectrum model has been applied in mountain areas. An underlying assumption of the ROS-system is a gradient from the urban to wilderness allowing the planner to provide a spectrum of recreation opportunities. In contrast, the Swedish coastal areas consist of a discontinuous environment which challenges a zoning. Archipelagos are essentially discontinuous with respect to many of the important spatial variables. Zoning in the archipelagos in Sweden has so far followed a zoning logic from physical geography; the assumption being that the gradient from inner, wooded zones to outer treeless would also be a gradient from the more urban or human influenced cultural landscape to a more pristine, marine wilderness in the outer. In 2003, a questionnaire survey to visitors was conducted in the Luleå archipelago, Sweden. Based on the results, the study examines the spatialization of the visitor characteristics, the activity patterns etc in relation to the ongoing planning of the area. This paper explores the planning challenges in adapting zoning to cope with recreation and tourism development as well as with the other land and resources uses that municipal comprehensive planning is charged with. Thereby possible conflicts are identified, and the potential of zoning is explored.